ALTERAÇÕES DE DESIGN E USABILIDADE NO APLICATIVO MATHGO - Sauthier, Morgana Jaína; Mendonça, Bárbara Gündel; Padoin, Edson Luiz (Salão do Conhecimento, 2019)
Projeto de Extensão realizado no curso de Design da Unijuí